Protease activity during cell differentiation of the cellular slime mold Dictyostelium discoideum. - Fong, D (1978)
Individual aggregates, migrating pseudoplasmodia, and sorocarps of Dictyostelium discoideum were assayed for proteolytic activities by colorimetric and fluorometric techniques. Cathepsin D-like and cathepsin B-like acid protease activities were found to decrease throughout development, but the patterns of decrease were different for the two enzymes. A gradual decrease was found for cathepsin D, whereas a sharp decrease between aggregates and migrating pseudoplasmodia was detected for cathepsin B. By using microdissection techniques and fluorometric assays for amino acids and peptides, prestalk cells and prespore cells exhibited no difference in cathepsin D activity, whereas cathepsin B activity was higher in the prestalk cells. Similarly, stalk cells and spores in the sorocarps showed no difference in cathepsin D activity, but showed a fivefold higher cathepsin B activity in the stalk cells. This finding suggests a possible role for cathepsin B in stalk cell differentiation.